Functional constipation in infants and toddler: modern possibilities of using pro- and prebiotics - S. B. Krutikhina; N. A. Geppe; E. A. Yablokova; M. A. Kudryashova (Лечащий Врач, 2023)
One of the most common gastroenterological pathologies in childhood is constipation of functional origin. The frequency of constipation in children of the first year of life ranges from 10.7% to 17.6%. Constipation is considered as a rare, painful, difficult and/ or incomplete bowel movement with stools of varying degrees of density and diameter. When diagnosing constipation in young children, it is important to focus not only on the frequency of the stool, but also on its nature, using the Bristol stool consistency scale. Even with daily bowel movements, accompanied by painful sensations and dense feces, the condition must be regarded as constipation. Suggested triggers in the first year of life are most often related to dietary changes, previous intestinal infection, and the presence of anal fissures. After the first year, improper toilet training may be an additional factor. When toilet training is incorrect, children begin to retain feces, which leads to painful defecation, and further forms fear, leading to an even greater delay in defecation. For the prevention and correction of constipation in young children, the following points are important: the presence of support for the legs during defecation; Encouraging the child to consume more water, fruits and vegetables every day, as well as to get enough physical activity. In the diet therapy of functional constipation, the role of some probiotics (strains of Lactobacillus, Bifidobacterium lactis) and prebiotics (inulin, galacto- and fructooligosaccharides) has been proven.